The Analysis Characterization of Major Characters of Novel Carrie’s War by Nina Bawden through Implementing Feminist Approach - Ni Putu Sri Puspita Dewi (Journal of English Education, Literature and Linguistics, 2021)
This study is conducted to identify the struggle that found in the novel Carrie’s War by Nina Bawden. In this study the researcher used Feminist criticism based on the content of the story in Carrie's War by Nina Bawden. In Carrie's War there is a story that shows how Carrie survived with a new environment after being evacuated to Wales. This novel also tells Carrie's life which is full of challenges and new experiences that make Carrie must be able to pass it. Feminist criticism is literary criticism conveyed by feminist theory, or more broadly, by feminism politics. In criticizing a language, feminist criticism uses the principles and ideology of feminism. This study is used qualitative method to analyze the charactaerization from each major characters. The researcher use three major characters such as Carrie Willow, Nick Willow, and Mr. Evans.